Mariology in the Euchology of Advent and Christmas in the Hispanic-Mozarabic Rite - Porosło, Krzysztof (Verbum Vitae, 2024)
This article, dedicated to the Mariology of the Hispanic-Mozarabic Missal during the Advent and Christmas seasons, has two objectives. First, it is intended to make the Mozarabic dogmatic sensibility, which is virtually unknown to theologians, more accessible. Second, it aims to extract the original Hispanic/Mozarabic Mariology from the euchology and to present it in a synthetic form. The article will present the history of the formation of Marian feasts in the Visigothic rite and analyse, from the Mariological perspective, the euchology of the feasts of the Immaculate Conception of Mary (8 December) and of the Blessed Virgin Mary (18 December), as well as the forms of the mass for the Second Sunday of Advent and for Christmas Day. It ends with a summary that points to the restraint of the Mozarabic tradition with respect to the number of Marian feasts, which coexists with the theological and dogmatic richness of the forms for these feasts. In the Hispanic tradition, Mary is virtually always presented in the context of her mission of virgin motherhood. At the same time, the Hispanic tradition frequently juxtaposes the figures of Mary-Mother and Church-Mother, demonstrating, in the spirit of the Augustinian theology, that what was accomplished in Mary is surpassed in the Church.